Model-Based Control Design and Integration of Cyberphysical Systems: An Adaptive Cruise Control Case Study - Emeka Eyisi; Zhenkai Zhang; Xenofon Koutsoukos; Joseph Porter; Gabor Karsai; Janos Sztipanovits (Journal of Control Science and Engineering)
The systematic design of automotive control applications is a challenging problem due to lack of understanding of the complex and tight interactions that often manifest during the integration of components from the control design phase with the components from software generation and deployment on actual platform/network. In order to address this challenge, we present a systematic methodology and a toolchain using well-defined models to integrate components from various design phases with specific emphasis on restricting the complex interactions that manifest during integration such as timing, deployment, and quantization. We present an experimental platform for the evaluation and testing of the design process. The approach is applied to the development of an adaptive cruise control, and we present experimental results that demonstrate the efficacy of the approach.